The Immune Protection Induced by a Serine Protease Inhibitor From the Foodborne Parasite Trichinella spiralis - Song, Yan Y.; Zhang, Yao; Yang, Daqi; Ren, Hua N.; Sun, Ge G.; Jiang, Peng; Liu, Ruo D.; Zhang, Xi; Cui, Jing; Wang, Zhong Q. (Frontiers in Microbiology, 2018)
Serine protease inhibitors (SPI) are a superfamily of the proteins able to suppress serine protease activity, and may exert the major biological function in complement activation, inflammation, and fibrinolysis. A SPI was identified from T. spiralis adult worms (AW) by immunoproteomics with early infection sera. The aim of this study was to investigate the protective immune elicited by TsSPI. The complete TsSPI cDNA sequence was cloned into pQE-80L and then expressed in Escherichia coli BL21. The rTsSPI was purified and its antigenicity was determined by Western blotting analysis. By using anti-rTsSPI serum the native TsSPI was identified in somatic and ES proteins from muscle larvae (ML). The results of qPCR and immunoﬂuorescence assay (IFA) revealed that the expression of the TsSPI gene was observed throughout all developmental stages of T. spiralis (ML, intestinal infective larvale, 3- and 6-day AW, and newborn larvae), located principally in cuticles, stichosome and embryos of this parasitic nematode. Vaccination of mice with rTsSPI triggereda high level of anti-TsSPI IgG response, and showed a 62.2% and 57.25% worm burden reduction in the recovery of intestinal AW at 6 days post infection (dpi) and muscle larvae at 35 dpi, respectively. The TsSPI might be a novel potential target for anti-Trichinella vaccine.